TMEM196 acts as a novel functional tumour suppressor inactivated by DNA methylation and is a potential prognostic biomarker in lung cancer - Liu, Wen-bin (Oncotarget, 2015)
Epigenetic silencing of tumour suppressors contributes to the development and progression of lung cancer. We recently found that TMEM196 was hypermethylated in lung cancer. This study aimed to clarify its epigenetic regulation, possible roles and clinical significance. TMEM196 methylation correlated with loss of protein expression in chemical-induced rat lung pathologic lesions and human lung cancer tissues and cell lines. 5-aza-2′-deoxycytidine restored TMEM196 expression. Moreover, TMEM196 hypermethylation was detected in 61.2% of primary lung tumours and found to be associated with poor differentiation and pathological stage of lung cancer. Functional studies showed that ectopic re-expression of TMEM196 in lung cancer cells inhibited cell proliferation, clonogenicity, cell motility and tumour formation. However, TMEM196 knockdown increased cell proliferation and inhibited apoptosis and cell-cycle arrest. These effects were associated with upregulation of p21 and Bax, and downregulation of cyclin D1, c-myc, CD44 and β-catenin. Kaplan–Meier survival curves showed that TMEM196 downregulation was significantly associated with shortened survival in lung cancer patients. Multivariate analysis showed that patients with TMEM196 expression had a better overall survival. Our results revealed for the first time that TMEM196 acts as a novel functional tumour suppressor inactivated by DNA methylation and is an independent prognostic factor of lung cancer.